Carbon Dot–Doped Titanium Dioxide Sheets for the Efficient Photocatalytic Performance of Refractory Pollutants - Shen, Shen; Li, Rong; Wang, Hongbo; Fu, Jiajia (Frontiers in Chemistry, 2021)
Broad solar light harvesting and fast photoinduced electron-hole migration are two critical factors for the catalytic capacity of photocatalytic system. In this work, a novel visible light-driven carbon dots-TiO2 sheets (CDs-TNs) photocatalyst was successfully prepared by loading CDs on the surface of TNs through hydrothermal method. The microstructure, chemical components, and optical properties of the prepared samples were characterized via X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscopy, UV-visible diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy analysis. Congo-red (CR), rhodamine B (RhB) and tetracycline (TC) were used as pollutants to assess the catalytic performance of CDs-TNs. As expected, the removal efficiencies of CDs-TNs for CR, RhB and TC are 94.6% (120min), 97.2% (150min), and 96.1% (60min) respectively, obviously higher than that of pure TNs. The enhanced degradation efficiency of CDs-TNs is predominantly ascribed to the merits of CDs (excellent up-conversion property and electron transfer property). Moreover, according to the several degradation cycles, CDs-TNs possessed the excellent stability, having removed 93.3% of CR after 120min irradiation.